Drainage Capillary Pressure Distribution and Fluid Displacement in a Heterogeneous Laminated Sandstone. Issue 14 (20th July 2021) - Lin, Qingyang; Bijeljic, Branko; Raeini, Ali Q.; Rieke, Holger; Blunt, Martin J.
Abstract: We applied three‐dimensional X‐ray microtomography to image a capillary drainage process (0–1, 000 kPa) in a cm‐scale heterogeneous laminated sandstone containing three distinct regions with different pore sizes to study the capillary pressure. We used differential imaging to distinguish solid, macropore, and five levels of subresolution pore phases associated with each region. The brine saturation distribution was computed based on average CT values. The nonwetting phase displaced the wetting phase in order of pore size and connectivity. The drainage capillary pressure in the highly heterogeneous rock was dependent on the capillary pressures in the individual regions as well as distance to the boundary between regions. The complex capillary pressure distribution has important implications for accurate water saturation estimation, gas and/or oil migration and the capillary rise of water in heterogeneous aquifers. Plain Language Summary: Carbon‐dioxide storage, hydrocarbon migration, and the capillary rise of water in heterogeneous aquifers and reservoirs are all controlled by capillary pressure. The capillary pressure varies dependent on the pore‐space heterogeneity. We used X‐ray microtomography to image capillary drainage in a laminated sandstone as an exemplar of a highly heterogeneous rock. The distribution of capillary pressure and pore‐scale configuration of fluid during displacement were measured and related to distinct heterogeneities in the rock. Differential imaging is used to characterize the larger macropores and subresolution porosity. We show that fluid displacement is controlled by pore size, connectivity, and proximity to the boundaries between regions with different pore‐space characteristics. Our study demonstrates how to characterize the complex capillary pressure distribution and fluid displacement in highly heterogeneous porous media. Key Points: The pore space, including subresolution pores, was divided into three regions with different heterogeneity for a laminated sandstone The capillary pressure distribution, influenced by pore size and connectivity, had distinct displacement behavior in different regions The trends in capillary pressure and displacement were measured across the boundaries between regions